2008
DOI: 10.12693/aphyspola.113.1245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gravitation on Water Migration in Granular Media

Abstract: The results of the experiments on water migration in unsaturated granular media performed with dynamic neutron radiography technique are presented. It was found that the porosity of the medium did not determine the kinetics of the process in a marked way. The influence of gravity was found to be considerable for media like coarse sand and gravel, consisting of large grains. No effect of gravitation on the water migration in clay beds was observed. The results are discussed in terms of the classical WashburnBos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Dry samples were placed inside a thermal chamber ( Fig. 1b) with double thermal shields [7,10]. The ambient temperature of the sample (T s ) was chosen to be 30, 40, 50, 60, or 70 • C and was stabilized within ±0.1 • C. Four K-type steel sheathed thermocouples of 0.5 mm diameter were inserted into each sample at dierent distances (x 1 = 11.3, x 2 = 30.7, x 3 = 51.3, x 4 = 101 mm) from their lower end (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Dry samples were placed inside a thermal chamber ( Fig. 1b) with double thermal shields [7,10]. The ambient temperature of the sample (T s ) was chosen to be 30, 40, 50, 60, or 70 • C and was stabilized within ±0.1 • C. Four K-type steel sheathed thermocouples of 0.5 mm diameter were inserted into each sample at dierent distances (x 1 = 11.3, x 2 = 30.7, x 3 = 51.3, x 4 = 101 mm) from their lower end (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Spontaneous capillary imbibition is a transport phenomenon present in a variety of technological applications such as oil recovery, building materials, soil science, textile and hydrology [1]. Due to this diversity of applications, an infinity of theoretical [2][3][4][5][6] and experimental [7][8][9][10][11][12][13][14] studies have been carried out based on the pioneering works of Lucas [15] and Washburn [16] in order to understand the imbibition mechanism and the related phenomena (for review, see [1,17,18], and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…It was experimentally demonstrated that the imbibition speed becomes slower than that of Lucas-Washburn Regime (x ∝ √ t) [7][8][9][10][11][12][13][14] as a consequence of the heterogeneity of flow in porous media due to the complex network of randomly distributed pores that connect to each other forming tortuous capillaries through which fluid flows. This tortuous path has a fractal character and the Lucas-Washburn equation is scarce to model imbibition process in permeable materials that possess fractal architecture.…”
Section: Introductionmentioning
confidence: 99%